KONTRIBUSI PERSEPSI SOSIAL TERHADAP INTERAKSI SOSIAL MAHASISWA - Monalisa Monalisa (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2017)
The background of this research was the importance of a college students’ guidance and counseling program in STKIP PGRI West Sumatera to have a good social interaction. Social perceptions became factors that can predictaffect social interaction. The purpose of this research was obviously to describe: (1) social perception, (2) social interaction, (3) the contribution of social perception towards social interaction. This research was using quantitative method with correlation type. The population was college students’ guidance and counseling program in STKIP PGRI West Sumatera in academic year 2012, 2013, 2014, and 2015. A number of college students were 818 students. The sample was 272 students selected by proportional stratified random sampling technique. The instrument was a Likert scale models. The research findings shown that: (1) social perceptions of the college students were in the positive category, (2) college students’ social interaction were in the good category,and (3) there was a significant contribution of social perception toward social interaction. Implications of these results can be used as an analysis of the college students’ needs in the preparation of guidance and counseling program services at universities, especially in STKIP PGRI West Sumatera.